Perkembangan dan Transformasi Metodologi Hadis pada Periode Klasik, Pertengahan, dan Modern - Ifroh Ritonga; M. Faridh; Farid Adnir (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Hadith is the second source of Islamic law after the Qur'an and serves to explain various aspects of Islamic teachings, including worship, social transactions, and moral conduct. Over time, the methodology of Hadith studies has undergone significant developments as an effort to preserve its authenticity, validity, and reliability, ensuring its continued relevance for Muslims. This study employs a qualitative approach using a library research method by collecting and analyzing various literature sources, including books on Hadith sciences, scholarly journals, and previous studies related to the development of Hadith methodology. The findings reveal that during the classical period, Hadith studies focused on oral transmission and rigorous memorization, emphasizing the integrity and credibility of narrators as the primary criteria for determining the authenticity of Hadith. In the medieval period, Hadith methodology became more systematic through the formulation of principles for sanad (chain of transmission) and matn (text) criticism, as well as the classification of Hadith into sahih (authentic), hasan (good), and da‘if (weak) categories based on established criteria. In the modern period, Hadith studies have expanded beyond traditional approaches by incorporating historical, sociological, and contextual perspectives to better understand Hadith in response to contemporary societal dynamics. Therefore, Hadith methodology has developed dynamically across different periods while maintaining its fundamental commitment to preserving the authenticity of Hadith as a primary source of Islamic teachings.